2022
DOI: 10.1186/s12889-022-13352-0
|View full text |Cite
|
Sign up to set email alerts
|

A study protocol of the adaptation and evaluation by means of a cluster-RCT of an integrated workplace health promotion program based on a European good practice

Abstract: Background An integrated workplace health promotion program (WHPP) which targets multiple lifestyle factors at different levels (individual and organizational) is potentially more effective than a single component WHPP. The aim of this study is to describe the protocol of a study to tailor a European good practice of such an integral approach to the Dutch context and to evaluate its effectiveness and implementation. Methods This study consists of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Simons et al's (2015) study from the Netherlands may offer a more controlled setting with its RCT involving Delft University employees, while Kowalski et al's (2024) Swedish study shines through its large sample of 1267 healthcare workers, who partook in a mHealth stress-management study. The Dutch protocol of study by Smit et al (2022) cut across sectors, where employees working in organizations that were completely unrelated to each other engaged with a workplace health promotion program. Appraising the EMPOWER intervention in their protocols of studies, Olaya et al (2022) Therefore, the varying layers of employment, as well as sectors and even national contexts indicated by these sets of characteristics, demonstrate the potential capacity for digital health interventions but also underline both their likely appeal to a broad audience on the basis of the problems they help solve and the particular adaptability such solutions are expected to possess in order to conform to a wide range of occupational health needs.…”
Section: Participant Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Simons et al's (2015) study from the Netherlands may offer a more controlled setting with its RCT involving Delft University employees, while Kowalski et al's (2024) Swedish study shines through its large sample of 1267 healthcare workers, who partook in a mHealth stress-management study. The Dutch protocol of study by Smit et al (2022) cut across sectors, where employees working in organizations that were completely unrelated to each other engaged with a workplace health promotion program. Appraising the EMPOWER intervention in their protocols of studies, Olaya et al (2022) Therefore, the varying layers of employment, as well as sectors and even national contexts indicated by these sets of characteristics, demonstrate the potential capacity for digital health interventions but also underline both their likely appeal to a broad audience on the basis of the problems they help solve and the particular adaptability such solutions are expected to possess in order to conform to a wide range of occupational health needs.…”
Section: Participant Characteristicsmentioning
confidence: 99%
“…Simons et al (2015) created a clear RCT structure with the effect that this reduces likely attrition, though self-selection issues combined with reliance on self-reporting may have skewed dropout rates. Smit et al (2022) and Olaya et al (2022) conducted research on the workplace health promotion program evaluation and assessment of eHealth intervention effectiveness without reporting details of attrition, which are often overlooked in the reports published. Thomson et al (2023) reported recruitment participation from 24 organizations and data received from 224 line managers for analysis, indicating reasonable participation rates, but the attrition rates were not specified.…”
Section: Attrition Ratesmentioning
confidence: 99%
“…The integrated WHPP to be implemented exists of (1) a catalogue with health promoting activities on multiple levels (individual and organizational) and multiple lifestyle themes (physical activity, nutrition, relaxation, smoking, work-life balance, alcohol consumption, stress and sleep) and (2) an implementation plan to support successful implementation (Smit et al 2022). The choice for these lifestyle themes was based on relevance according to both employers and employees.…”
Section: The Integrated Whppmentioning
confidence: 99%
“…This study was embedded in a larger study in which an integrated WHPP will be developed, implemented and evaluated (Smit et al 2022). Organizations that will participate in the cluster randomized controlled trial (c-RCT) to evaluate the integrated WHPP were recruited trough the network of the research team, co-workers and branch specific networks and platforms.…”
Section: Recruitmentmentioning
confidence: 99%
See 1 more Smart Citation